The enterotoxigenicity of strains of Escherichia coli isolated from the faeces of healthy people and cattle. - Bettelheim, K. A. (Cambridge University Press, 1982)
In this study 197 strains of Escherichia coli isolated from cowpats and the faeces of healthy humans were examined for the presence of enterotoxins. Six strains representing five different serotypes were found to be enterotoxigenic. Four of these strains produced the heat labile enterotoxin and two, the Vero cell cytotoxin.